Analisis Pengaruh Kualitas Pelayanan, Biaya Dan Fasilitas Terhadap Kepuasan Pasien Rawat Jalan Rumah Sakit Benyamin Guluh Kolaka - Nadillah Nurahma; Fitri Kumalasari; Suwarto Suwarto (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this study is to determine the analysis of the effect of service quality, costs and facilities on the satisfaction of outpatient patients Benyamin Guluh Kolaka This research is a survey research using a questionnaire as an instrument. The population in this research is all patients who have carried out outpatient treatment at Benjamin Guluh Kolaka Hospital in Kolaka Regency and taken as many as 75 responsiveness using purposive sampling techniques, namely the technique of determining certain criteria. Data collection techniques are primary data and secondary data. The data obtained were analyzed using PLS analysis techniques through Smart PLS software. The results of this study indicate that service quality has a positive and significant effect on patient satisfaction. This is evidenced by T-count or T-statistics which is 2.164 higher than the rule of thumb used which is 1.96 and the cost also has a positive and significant effect on patient satisfaction due to the value of T-count or T-Statistics which is 13.769 higher than the rules of thumb used is 1.96. While the facility has a negative and not significant effect on patient satisfaction because the value of t arithmetic or t statistical value is 1.089 lower than the rule of thumb used that is 1.96 then the service quality variable and the cost have a positive and significant effect on passient satisfaction of 97.1%.